Determining the elements in supply chain model of the Malaysia agricultural co-operatives - Idris, Nurjihan; Mohamed Arshad, Fatimah; Radam, Alias; Ali, Noor Azman (Co-operative College of Malaysia, 2013)
In Malaysia, cooperatives are viewed as a developing sector, yet agricultural cooperatives are still lagging behind in terms of a number of factors mainly in supply chain system. Thus, this study attempts to examine the elements contributing to the supply chain model in Malaysian agricultural cooperatives. The primary data is collected via survey using questionnaire from agricultural-based cooperatives, farmers' cooperatives and fishermen's cooperatives. Factor analysis and structural equations modeling were used to analyze the data. Findings show quality, technology and marketing, logistic, governance and quality of workforce, suppliers and optimum level of production, quality work life and efficient technology and experienced and trained worker are significant in determining the supply chain of Malaysian agricultural cooperatives.